2003
DOI: 10.1021/ma034173v
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Hydrophobic Interactions in Associative Polymers Using Inclusion Compounds and Surfactants

Abstract: We report the modulation of the solution rheology of a comblike, hydrobhobically modified alkali-soluble emulsion (HASE) associative polymer through addition of R-and β-cyclodextrins (CDs). The ring-shaped CDs with hydrophobic inner cores interact with the pendant macromonomer segments of the associative polymer containing hydrophobic end groups, leading to reduction in polymer solution viscosity and dynamic moduli by several orders of magnitude. We find no interactions between the CDs and the polymer backbone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 42 publications
5
62
0
Order By: Relevance
“…12 This concept is based on the idea of using cyclodextrin to encapsulate hydrophobic segments so that the molecular properties of single chain and the solution viscosity of associative polymers can be controlled. 13, 14 Karlson 15,16 proposed a simple Langmuir adsorption model for describing the complexation mechanism between cyclodextrin and hydrophobically modified PEO. They concluded that cyclodextrin molecules could complex with hydrophobic end groups of associative polymers resulting in the disruption of the three-dimensional associating network.…”
Section: Introductionmentioning
confidence: 99%
“…12 This concept is based on the idea of using cyclodextrin to encapsulate hydrophobic segments so that the molecular properties of single chain and the solution viscosity of associative polymers can be controlled. 13, 14 Karlson 15,16 proposed a simple Langmuir adsorption model for describing the complexation mechanism between cyclodextrin and hydrophobically modified PEO. They concluded that cyclodextrin molecules could complex with hydrophobic end groups of associative polymers resulting in the disruption of the three-dimensional associating network.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicated the formation of complex in a 1:1 stoichiometric ratio. Abdala et al [32] calculated the stoichiometric ratio of a complex formed between cyclodextrin and a macromonomer using the integral area under the 1 H proton of the 1 H NMR.…”
Section: H Nmr Spectroscopymentioning
confidence: 99%
“…The nature of association mechanism and the conformation of polymer chains in solution are controlled by the equilibrium between the hydrophobic attraction and the electrostatic repulsion. It has been observed that these aggregates could be destroyed by the addition of excess amounts of surfactants or β‐cyclodextrin 10–13, 24…”
Section: Introductionmentioning
confidence: 98%